Difference between revisions of "008A Sample Final A, Question 11"
Jump to navigation
Jump to search
(One intermediate revision by the same user not shown) | |||
Line 2: | Line 2: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | !Foundations | + | !Foundations: |
|- | |- | ||
|1) How many fractions will this decompose into? What are the denominators? | |1) How many fractions will this decompose into? What are the denominators? | ||
Line 18: | Line 18: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 1: | + | !Step 1: |
|- | |- | ||
|From the factored form of the denominator we can observe that there will be three denominators: <math>x - 1, x + 3</math>, and <math>(x + 3)^2</math>. So the final answer with have the following form: <math>\frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math> | |From the factored form of the denominator we can observe that there will be three denominators: <math>x - 1, x + 3</math>, and <math>(x + 3)^2</math>. So the final answer with have the following form: <math>\frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math> | ||
Line 24: | Line 24: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 2: | + | !Step 2: |
|- | |- | ||
− | |Now we have the equality <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>. | + | |Now we have the equality <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>. We clear the denominators and end up with <math>A(x + 3)^2 + B(x - 1)(x + 3) + C(x - 1) = 3x^2 + 6x + 7</math>. |
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 3: | + | !Step 3: |
|- | |- | ||
− | | | + | |By evaluation both sides by using x = 1, we will zero out the B and C. This leads to <math>A(1 + 3)^2 = 3(1)^2 + 6(1) + 7, 16A = 3 + 6 + 7</math> , and finally <math>A = 1</math>. |
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 4: | + | !Step 4: |
|- | |- | ||
− | |Now | + | |Now evaluating at x = -3 to zero out both A and B. This yields the following equations <math>C((-3) - 1) = 3(-3)^2 + 6(-3) + 7</math>, <math>-4C = 3(9) - 18 + 7</math>, <math>-4C = 27 - 11</math>, and <math>C = -4</math> |
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 5: | + | !Step 5: |
|- | |- | ||
− | |To obtain the value of B we can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us <math>A(0 + 3)^2 + B(0 - 1)(0 + 3) + C(0 - 1) = 9A -3B -C = 7</math>. However, we know the values of both A and C, which are 1 and -4, respectively. So <math>9 -3B - (-4) = 7</math>, <math>-3B + 13 = 7</math>, <math>-3B = -6</math>, and finally <math>B = 2</math>. | + | |To obtain the value of B we can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us <math>A(0 + 3)^2 + B(0 - 1)(0 + 3) + C(0 - 1) = 9A -3B -C = 7</math>. However, we know the values of both A and C, which are 1 and -4, respectively. So <math>9 -3B - (-4) = 7</math>, <math>-3B + 13 = 7</math>, <math>-3B = -6</math>, and finally <math>B = 2</math>. |
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Final Answer: | + | !Final Answer: |
|- | |- | ||
|<math>\frac{1}{x - 1} + \frac{2}{x + 3} - \frac{4}{(x + 3)^2}</math> | |<math>\frac{1}{x - 1} + \frac{2}{x + 3} - \frac{4}{(x + 3)^2}</math> |
Latest revision as of 22:58, 25 May 2015
Question: Decompose into separate partial fractions
Foundations: |
---|
1) How many fractions will this decompose into? What are the denominators? |
2) How do you solve for the numerators? |
Answer: |
1) Since each of the factors are linear, and one has multipliclity 2, there will be three denominators. The linear term, , will appear once in the denominator of the decomposition. The other two denominators will be . |
2) After writing the equality, , clear the denominators, and evaluate both sides at x = 1, -3, and any third value. Each evaluation will yield the value of one of the three unknowns. |
Solution:
Step 1: |
---|
From the factored form of the denominator we can observe that there will be three denominators: , and . So the final answer with have the following form: |
Step 2: |
---|
Now we have the equality . We clear the denominators and end up with . |
Step 3: |
---|
By evaluation both sides by using x = 1, we will zero out the B and C. This leads to , and finally . |
Step 4: |
---|
Now evaluating at x = -3 to zero out both A and B. This yields the following equations , , , and |
Step 5: |
---|
To obtain the value of B we can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us . However, we know the values of both A and C, which are 1 and -4, respectively. So , , , and finally . |
Final Answer: |
---|